2017
DOI: 10.1080/13697137.2017.1284782
|View full text |Cite
|
Sign up to set email alerts
|

An International Menopause Society study of vasomotor symptoms in Bangkok and Chiang Mai, Thailand

Abstract: HFNS reports are prevalent with moderate frequency and problem-ratings in these urban centers in Thailand. The results will be included in the broader International Menopause Society study of Climate, Altitude and Temperature (IMS-CAT) of the impact of climate on HFNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…About 21 million women living in the USA today and 1.1 billion women worldwide by 2025 will experience menopausal symptoms [1][2][3][4][5], which begin when menses become irregular or stop [1,6]. Menopausal symptoms can last for 10 to 15 years [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…About 21 million women living in the USA today and 1.1 billion women worldwide by 2025 will experience menopausal symptoms [1][2][3][4][5], which begin when menses become irregular or stop [1,6]. Menopausal symptoms can last for 10 to 15 years [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…The multiethnic, community-based Study of Women’s Health Across the Nation (SWAN) [ 33 35 ] reported that vasomotor symptoms were more prevalent among African-American and Hispanic women and less prevalent among Japanese-American and Chinese-American women than white women. As the most important vasomotor symptom, emerging analyses of studies revealed that the prevalence of hot flashes in Asian women is similar to those of Western countries [ 36 , 37 ]. As a result, the current study’s pooled estimates of different continents find that women in Africa with highest prevalence of hot flashes, whereas women in Asia, Europe, and North America are of comparable prevalence, which validates prior studies [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These everyday symptoms will affect 75% of women, 1 or about 21 million women living in the United States today and 1.1 billion women around the world by 2025. [1][2][3][4][5] The sudden rush of heat and sweating that defines hot flashes lasts only minutes but these symptoms typically persist for 7 years (range = 0 to 15+ years). 1,6 There is a preponderance of myths, misinformation, and negative imagery surrounding menopausal hot flashes.…”
Section: Introductionmentioning
confidence: 99%